STRATEGI KOMUNIKASI POLISI SEKTOR (POLSEK) LABUAN UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM MENCIPTAKAN MASYARAKAT SADAR KEAMANAN DAN KETERTIBAN MASYARAKAT (KAMTIBMAS) - Badaruddin, Widya Castra (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2019)
The purpose of this study is to find out the Communication Strategy and the obstacles of the Labuan Police Sector to Increase Community Participation in Creating A Community Awareness of Public Order and Security (KAMTIBMAS). The type of research used is descriptive qualitative type. The basis of the research in this study is a case study with a total of 5 (five) informants, data collection techniques used are observation and in-depth interviews. The data analysis technique used is descriptive qualitative. The results showed that the communication strategy of the Labuan Sector Police in carrying out KAMTIBMAS activities in its jurisdiction was to identify the communication target which consisted of a reference frame factor from the community background and situation and condition factors sourced from the data and information of the Kamtibmas Supervisory Officer of each village. The study of the purpose of communication messages by the Polsek is generally a message about security and order, the implementation of KAMTIBMAS activities cannot be separated from the media, namely loudspeakers, focus groups, posters and the last component is divided into two aspects, namely the attractiveness of the Polsek and the credibility of the Police or public trust. The inhibiting factors or disruptions to the police communication strategy are technical problems, communication media, namely loudspeakers and infocus audio media, which still depend on electricity. The two semantic disorders are errors in the language used by the Labuan Police so that the audience has difficulty in capturing the message conveyed, this is related to the background of the audience that has not been considered. Lastly, physical obstacles caused by geographical conditions especially during the rainy season.